Improved relapse‐free survival after autologous stem cell transplantation does not translate into better quality of life in chronic lymphocytic leukemia: Lessons from the randomized European Society for Blood and Marrow Transplantation‐Intergroup study. Issue 2 (February 2014) - de, Liesbeth C.; Watson, Maggie; van, Marleen; Milligan, Donald; van, Michel; Michallet, Mauricette; Dreger, Peter; Dearden, Claire E.; Homewood, Janis; Dupuis, Jehan; Leporrier, Michel; Karas, Michal; et al.
<x xml:space="preserve">Abstract</x> In chronic lymphocytic leukemia (CLL) medical progress is driven by clinical studies with relapse‐free survival (RFS) as the primary endpoint. The randomized EBMT‐Intergroup trial compared high‐dose therapy and autologous stem cell transplantation (ASCT) to observation and demonstrated a substantial improvement of RFS without showing improved overall survival for the transplant arm. Here we report quality of life (QoL) information of the first 3 years following randomization from that study. The main objective was to assess the impact of treatment on QoL over time. Two secondary analyses were performed to further investigate the impact of ASCT and relapse on QoL. In the primary analysis, we demonstrate an adverse impact of ASCT on QoL which was largest at 4 months and continued throughout the first year after randomization. Further, we demonstrated a sustained adverse impact of relapse on QoL which worsened over time. Despite better disease control by ASCT the side effects thus turned the net effect towards inferior QoL in the first year and comparable QoL in the following 2 years after randomization. This study emphasizes the importance of information concerning QoL impacts when patients are counseled about treatments aimed at improving RFS in the absence of a survival benefit. Am. J. Hematol. 89:174–180, 2014. © 2013 Wiley Periodicals, Inc.